Validity, reliability of Greek version of Richmond agitation-sedation scale (RASS) among critically ill patients. - Anastasios Tzenalis; Christina Zamouridoy; Despoina Agorogianni; Asimenia Dadana (Ene, 2016)
Introduction: The majority of critically ill patients experience significant distress, anxiety, and agitation which is often seen with administration of excessive sedation. Although sedation-agitation scales are commonly used in Greek ICU practice, there is no report evaluating the clinical usefulness of these scales in the Greek language. Objective: The objective of this study was to evaluate the validity and reliability of Greek translation of the Richmond Agitation-Sedation Scale (RASS) among critically ill patients. Methodology: This is a validation study carried out in the ICU of Papageorgiou General Hospital. The RASS scale translated in accordance with international guidelines' of clinical adaptation group and applied to 100 patients from four nurses. The nursing team examined the reliability of this tool evaluating the inter-raters reliability and calculating the coefficient kappa. While the validity of the conceptual structure was confirmed by the degree of correlation between the new translated tool and two existing valid tools: the «Ramsay Sedation Scale» (RSS) and the «Riker Sedation Agitation Scale» (SAS). Results: 400 observations were made on 100 patients. All scales had at least substantial agreement (wK 0,78- 0,93). The RASS (Wk 0,78-0,92) and SAS (Wk 0,82-0,91) showed the biggest agreement. The credibility among researchers in the RASS and SAS scales showed a very good level (> 0.80) in the measurements of all the research team members. There was at least a moderate correlation (r> 0.7 or <-0.7) with statistical significance (p <0.001) between all three scales. The highest correlation emerged between SAS, and RASS. Conclusions: The RASS and SAS scales showed higher levels of correlation and agreement between them in connection with the RSS. The Greek translation of the RASS scale demonstrated validity and reliability and can be used in clinical practice in order to reduce the negative impacts of over sedation and agitation.